The Impact of Entrepreneurship Education Programs (EEPs) on Students' Entrepreneurial Interests - Taufik Samsuri; Saiful Prayogi; Ni Nyoman Sri Putu Verawati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study delves into the impact of Entrepreneurship Education Programs (EEPs) at universities on fostering students' entrepreneurial interests, employing a qualitative approach to gauge the effectiveness of these programs. Through in-depth interviews with 20 students participating in an EEP at a private university, the research uncovers a significant gap between the theoretical knowledge imparted by these programs and the practical skills and motivations needed to pursue entrepreneurship. The findings reveal that while students value the theoretical underpinnings of entrepreneurship taught in these programs, the lack of hands-on, experiential learning opportunities and direct engagement with successful entrepreneurs leaves them feeling underprepared and insufficiently inspired to embark on entrepreneurial ventures. Students expressed a strong desire for EEPs to incorporate more real-world applications, such as internships, project collaborations, and mentorship from seasoned entrepreneurs, to bridge the gap between academic learning and practical entrepreneurial experience. The study concludes with recommendations for universities to redesign EEPs to include a greater emphasis on experiential learning and engagement with the entrepreneurial ecosystem, aiming to better equip students with the entrepreneurial mindset, skills, and networks necessary to succeed in their entrepreneurial endeavors. By highlighting these insights, the study contributes to the ongoing discourse on the optimization of entrepreneurship education to more effectively cultivate the next generation of innovators and entrepreneurs, underscoring the need for a more integrated approach that balances theoretical knowledge with practical application and inspiration.